2008
DOI: 10.1097/01.nne.0000299496.23119.68
|View full text |Cite
|
Sign up to set email alerts
|

A Responsive Evaluation of an Aboriginal Nursing Education Access Program

Abstract: Nursing education access programs have been introduced in a number of countries to address the shortage of healthcare providers of Aboriginal descent. An evaluation study of a nursing education access program in Labrador, Canada, was undertaken using a Responsive Evaluation approach. Interviews and focus groups with program stakeholders were conducted. Program effectiveness was influenced by culturally relevant curriculum, experiential and authentic learning opportunities, academic and social support, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In addition, several other scholars, including Jalili-Grenier and Chase (1997), Malu and Figlear (2001) and Dhaliwal (2009), found that facilitating the use of all senses, visualization in particular, proved successful. As Meehan-Andrews (2009) and Curran et al (2008) recently confirmed, educators are well aware of health care students' preference for practical, hands-on methods of learning.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, several other scholars, including Jalili-Grenier and Chase (1997), Malu and Figlear (2001) and Dhaliwal (2009), found that facilitating the use of all senses, visualization in particular, proved successful. As Meehan-Andrews (2009) and Curran et al (2008) recently confirmed, educators are well aware of health care students' preference for practical, hands-on methods of learning.…”
Section: Literature Reviewmentioning
confidence: 90%
“…A number of scholars have shown that students' experiences of interaction and atmosphere within the learning community proved significant for learning among culturally diverse health care students (Gardner, 2005;Chapman and Pyvis, 2006;Curran et al, 2008;Sanner and Wilson, 2008). They concluded it was important to get to know students and to foster an atmosphere that appreciates diversity.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Other researchers also indicated that instructional approaches must be adapted to Indigenous learners' knowledge base, and that students' contexts must be understood by instructors when teaching in order to promote learning (Curran et al, 2008;Pijl-Zieber & Hagen, 2011;Wilson et al, 2011). In an evaluation study about an Aboriginal nursing education access program in Labrador, Curran et al (2008) found that instructional methods such as storytelling, reflective exercises, and experiential activities promoted learning among Aboriginal students.…”
Section: Curricular Relevancementioning
confidence: 99%
“…In an evaluation study about an Aboriginal nursing education access program in Labrador, Curran et al (2008) found that instructional methods such as storytelling, reflective exercises, and experiential activities promoted learning among Aboriginal students.…”
Section: Curricular Relevancementioning
confidence: 99%